PPO.67 Atypical Pre-eclampsia with Post-Partum Cardiac Dysfunction. (9th June 2014) - Malone, C; Adams, B
Abstract : Atypical pre-eclampsia presents a diagnostic challenge without classic symptoms of hypertension and proteinuria; patients with atypical features may progress to unexpectedly severe disease as described below. Case 1: A 36 year old multipara with essential hypertension underwent elective caesarean section at 38 weeks gestation. Blood pressure was well controlled antenatally, without proteinuria. She was readmitted day four post-partum, developing progressive dyspnoea and orthopnoea. Investigations showed hypoxia and pulmonary oedema, responding to IV diuretics. Echocardiogram (previously normal) revealed mild left ventricular dilation with normal systolic function and ejection fraction (EF) 55%. Repeat echocardiogram nine days later following increased hypertension demonstrated moderate global impairment in systolic function with EF 45%. Subsequent normal coronary angiogram six months later and complete resolution of echocardiogram changes one year later led to a retrospective diagnosis of atypical pre-eclampsia. Case 2: A 36 year old multipara with a previous history of pre-eclampsia remained normotensive until elective delivery at 36 weeks gestation. She presented day six post-operatively with progressive dyspnoea, chest tightness and headaches. Blood pressure 154/91mmHg with trace proteinuria, PaO2 8.5 kPa and normal ECG. CTPA revealed moderate pleural effusions, symptoms improved with IV diuretics. Subsequent echocardiogram demonstrated moderate mitral regurgitation, borderline LV systolic function with EF 50–55%, with BNP of 2100- working diagnosis peripartum cardiomyopathy. This progressed in three days to severe mitral regurgitation on repeat echocardiogram, BNP reduced to 289. Four weeks post-discharge echocardiogram showed mild mitral regurgitation with normal left ventricular systolic function, EF 55%. Multidisciplinary discussion reached a diagnosis of atypical pre-eclampsia.